Electrophysiological correlates of word comprehension: event-related potential (ERP) and independent component analysis (ICA) - Mehta J; Jerger S; Jerger J; Martin J (International Journal of Audiology, 2009)
In this study we asked to what extent auditory evoked potentials can help us to understand the complex processes underlying word comprehension. Monosyllabic and bisyllabic words were presented to 34 young adults in the context of a semantic category judgment. The basic paradigm assessed the typicality effect, the tendency for classification of members of a category to be made more accurately and more rapidly for strong exemplars than for weak exemplars. Event-related potentials (ERPs) were recorded from 30 active scalp electrodes. The ERP waveform in response to the semantic categorization of a word was characterized by unique activity in four temporal intervals; (1) a negative peak at a latency of about 100 ms, (2) a positive peak at a latency of about 200 ms, (3) a broad negativity extending over the latency range from 200 to 600 ms, and (4) a broad positivity extending from 600 to 1400 ms. Independent component analysis (ICA) of the individual EEG epochs yielded four maximally independent components, interpreted as (1) exogenous detection of a change in the acoustic environment, followed by allocation of cognitive resources, especially sustained attention, to the analysis of subsequent acoustic events, (2) phonological processing, (3) semantic processing, and (4) decision processing. The morphologies of the four ICA waveforms were consistent with a parallel processing, interactive model of word recognition, and subsequent semantic categorization.